From Indium‐Doped Ag2S to AgInS2 Nanocrystals: Low‐Temperature In Situ Conversion of Colloidal Ag2S Nanoparticles and Their NIR Fluorescence. Issue 51 (13th August 2018) - Shang, Huishan; Di, Qiumei; Ji, Muwei; Bai, Bing; Liu, Jiajia; Chen, Wenxing; Xu, Meng; Rong, Hongpan; Liu, Jia; Zhang, Jiatao
Abstract: Focusing on ternary I‐III‐VI2 colloidal nanocrystals (NCs) synthesized with precise control of the composition (from doping to ternary composition) and NIR fluorescence performance, monodisperse binary In 3+ ‐doped Ag2 S NCs and ternary AgInS2 NCs have been achieved successfully by facile low‐temperature in situ conversion of colloidal Ag2 S nanoparticles. In 3+ ions were inserted into the crystal lattice of Ag2 S NCs at a relatively low temperature as dopant and ternary AgInS2 NCs were obtained at a higher temperature following a phase transition. These doped Ag2 S and AgInS2 NCs based on different indium precursor concentrations were explored with respect to the position and intensity of the near‐infrared photoluminescent emission at different doping levels and crystal phase evolution. Abstract : Tunable nanocrystals . Ternary I‐III‐VI2 (AgInS2 ) colloidal nanocrystals (NCs) with precise control of the composition (from In 3+ doping to ternary composition) and good NIR fluorescence performance (800–1000 nm) have been synthesized by facile low‐temperature in situ conversion of colloidal Ag2 S nanoparticles. In 3+ ions were inserted into the crystal lattice of Ag2 S NCs at a relatively low temperature as dopant with ternary AgInS2 NCs obtained at a higher temperature following a phase transition (see figure).